2020
DOI: 10.20944/preprints202001.0380.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of Sowing Date, Seed Rate and Row Spacing on Productivity and Profitability of Barley (<em>Hordeum vulgare</em>) in North India

Abstract: The precise information regarding the date of sowing, seed rate and row spacing is critical for achieving yield targets and better economic returns of barley. Therefore here, we determined the information regarding the optimum date of sowing, seed rate, spacing and economic aspects for barley production. This study was conducted for three years, in north Indian plains. Early sowing date of barley (last week of October) recorded higher yield in comparison to late sown crop (3rd week of November). Moreover, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
3
1
0
Order By: Relevance
“…It might be due to better genomics characters as well as better growth characteristics and yield attributes of the variety HD 2967 achieved under favorable climatic conditions. Similar findings were reported by Singh et al [30][31][32][33]27,34,35].…”
Section: Yieldsupporting
confidence: 90%
“…It might be due to better genomics characters as well as better growth characteristics and yield attributes of the variety HD 2967 achieved under favorable climatic conditions. Similar findings were reported by Singh et al [30][31][32][33]27,34,35].…”
Section: Yieldsupporting
confidence: 90%
“…Results of seeding rate, nitrogen fertilizer level and their interaction on barley 1000-grain weight are shown in Table 6, where no significant effects were observed between seeding rates and nitrogen fertilizer levels. However, the interaction between (200 seeds m -2 × 0 kg N ha -1 ) and (300 seed m -2 × 0 kg N ha -1 ) also 300 seed m -2 × 40 kg N ha -1 significantly influenced 1000-grain weight with 37 g, while 300 seeds m -2 × 40 kg N ha -1 had the lowest value with 33.33 g. These results are similar to Al-Freeh et al (2015), and Amarjeet et al (2020), which report that 1000-grain weight did not affect barley seeding rates; also, the results of the present experiment are in accord with Dubey et al (2018 b), Terefe et al (2018) and Guddisa et al (2020) results, which found no significant influence of nitrogen fertilizer on barley 1000 grain weight.…”
Section: Weightsupporting
confidence: 88%
“…The desirable effect on earliness characters, growth characters and yields and its attributes of barley as a result of planting barley on 10 th December might be imputed to the suitable environmental conditions during this period which play a vigorous protagonist in activating establishment and development of plants, hence increasing plant elevation. Confirming these findings, Amarjeet et al (2020), Shivhare et al (2020), Abd El-Lattief et al (2021 and Moustafa et al (2021).…”
Section: Effect Of Sowing Datessupporting
confidence: 55%
“…Delay in planting may results in low biomass production and poor grain development due to higher temperature conditions at the time of maturity (Abd El-Lattief et al, 2021). Amarjeet et al (2020) revealed that sowing barley in last week of October recorded higher yields in comparison to sowing in the 3 rd week of November. Shivhare et al (2020) found that sown barley on 15 th November recorded significantly higher grains number and weight per the spike, length of spike and 1000-grain weight over 5 th November and 25 th October sown.…”
Section: Introductionmentioning
confidence: 99%